Good days and bad days in dementia: a qualitative chart review of variable symptom expression. (August 2014) - Rockwood, Kenneth; Fay, Sherri; Hamilton, Laura; Ross, Elyse; Moorhouse, Paige
ABSTRACT Background: Despite its importance in the lived experience of dementia, symptom fluctuation has been little studied outside Lewy body dementia. We aimed to characterize symptom fluctuation in patients with Alzheimer's disease (AD) and mixed dementia. Methods: A qualitative analysis of health records that included notations on good days and bad days yielded 52 community-dwelling patients (women, n = 30; aged 39–91 years; mild dementia, n = 26, chiefly AD, n = 36). Results: Good days/bad days were most often described as changes in the same core set of symptoms (e.g. less/more verbal repetition). In other cases, only good or only bad days were described (e.g. no bad days, better sense of humor on good days). Good days were typically associated with improved global cognition, function, interest, and initiation. Bad days were associated with frequent verbal repetition, poor memory, increased agitation and other disruptive behaviors. Conclusions: Clinically important variability in symptoms appears common in AD and mixed dementia. Even so, what makes a day "good" is not simply more (or less) of what makes a day "bad". Further investigation of the factors that facilitate or encourage good days and mitigate bad days may help improve quality of life for patients and caregivers.